2021
DOI: 10.3390/cli9070120
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Hydroclimatic Intensity in Colombia

Abstract: Prediction of precipitation changes caused by global climate change is a practical and scientific problem of high complexity. To advance, we look at the record of all available rain gauges in Colombia and at the CHIRPS database to estimate trends in essential variables describing precipitation, including HY-INT, an index of the hydrologic cycle’s intensity. Most of the gauges and cells do not show significant trends. Moreover, the signs of the statistically significant trends are opposite between the two datas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…This challenge has been generally addressed with local‐scale management plans and strategies. However, in a region like Northern South America (particularly in Colombia), water, food and energy security (which largely supports the country's economy) depend, almost exclusively, on surface water which in turn is associated with short‐term rainfall generation processes (Álvarez‐Villa et al, 2011; Díaz et al, 2020; Mesa et al, 2021). The connection with the Pacific and Atlantic oceans, the Amazon–Andes interactions, and the orographic barrier of the regional Andes are the major drivers of atmospheric circulation and ecological diversity in the country (Espinoza et al, 2020; Hoyos, 2017; Poveda et al, 2014; Sakamoto, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This challenge has been generally addressed with local‐scale management plans and strategies. However, in a region like Northern South America (particularly in Colombia), water, food and energy security (which largely supports the country's economy) depend, almost exclusively, on surface water which in turn is associated with short‐term rainfall generation processes (Álvarez‐Villa et al, 2011; Díaz et al, 2020; Mesa et al, 2021). The connection with the Pacific and Atlantic oceans, the Amazon–Andes interactions, and the orographic barrier of the regional Andes are the major drivers of atmospheric circulation and ecological diversity in the country (Espinoza et al, 2020; Hoyos, 2017; Poveda et al, 2014; Sakamoto, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the technical study of the evidence of climate change by the Institute of Hydrology, Meteorology, and Environmental Studies (IDEAM) [35] delimits the areas of the country with a tendency to increase precipitation (Caribbean region, Orinoco, middle valleys of the Magdalena and Cauca rivers) and the areas with a tendency to decrease precipitation (insular zone, northeast of the country and the eastern slope of the Eastern Cordillera). Recently, Mesa et al [31] studied hydroclimatic trends at the national level and found positive trends in the North Pacific and the middle valley of Cauca, and negative trends in the eastern slope of the Eastern Cordillera, during 1981-2013, using rainfall stations and CHIRPS dataset. However, only 21% of the rainfall station and 25% of grids from CHIRPS showed significant trends over the country.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Colombia is a country highly susceptible and vulnerable to extreme weather events due to its location, the influence by the Inter-Tropical Convergence Zone (ITCZ), the three low-level jets, the Amazon, the topography, and different processes in both the Pacific and Atlantic oceans. The ENSO in both phases, warm (El Niño) and cold (La Niña), is one of the main phenomena that has the greatest effects on the national territory of Colombia [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This challenge has been generally addressed with local-scale management plans and strategies. However, in a region like Northern South America (particularly in Colombia), water, food and energy security (which largely supports the country's economy) depend, almost exclusively, on surface water, which in turn is associated with short-term rainfall generation processes (Álvarez-Villa, Vélez, & Poveda, 2011;Díaz, Saurral, & Vera, 2020;Mesa, Urrea, & Ochoa, 2021). In addition, Colombia is one of the most biodiverse regions in the world (Myers, Mittermeier, Mittermeier, Da Fonseca, & Kent, 2000;Churchill, 2009;Bruijnzeel, Scatena, & Hamilton, 2011;Herzog & Kattan, 2011;Ehrendorfer, 2013;Hutter, Lambert, & Wiens, 2017;Hoorn, Perrigo, & Antonelli, 2018;Bax & Francesconi, 2019).…”
Section: Introductionmentioning
confidence: 99%